2010
DOI: 10.1007/s12562-010-0236-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extracts from narezushi, a fermented mackerel product, on cholesterol metabolism in Wistar rats

Abstract: Narezushi extract was separated into peptide and nonpeptide fractions by ion-exchange column chromatography. The narezushi extract and fractions were administered to rats in a diet enriched with lipid and cholesterol for 30 days. In the narezushi extract and nonpeptide fraction groups, increases in triglyceride, total cholesterol, and low-density lipoprotein-cholesterol levels in the plasma and accumulation of total lipids and triglyceride in the liver were suppressed, while both lipid and cholesterol fecal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 34 publications
2
18
0
1
Order By: Relevance
“…We already reported that the administration of the heshiko and narezushi extracts decreased systolic blood pressure and ACE activity in the aorta and plasma in the spontaneously hypertensive rat (26,27). Furthermore, the increases in plasma cholesterol and triacylglycerol levels in the rats fed the high-fat experimental diet were also suppressed by the administration of heshiko and narezushi extracts (28,29). In the rats administered heshiko and narezushi extracts, the PAI-1 activity of plasma decreased despite the difference in diet (data not shown).…”
Section: The Effect Of Heshiko and Narezushi Extracts On Fi Brinolytimentioning
confidence: 86%
See 3 more Smart Citations
“…We already reported that the administration of the heshiko and narezushi extracts decreased systolic blood pressure and ACE activity in the aorta and plasma in the spontaneously hypertensive rat (26,27). Furthermore, the increases in plasma cholesterol and triacylglycerol levels in the rats fed the high-fat experimental diet were also suppressed by the administration of heshiko and narezushi extracts (28,29). In the rats administered heshiko and narezushi extracts, the PAI-1 activity of plasma decreased despite the difference in diet (data not shown).…”
Section: The Effect Of Heshiko and Narezushi Extracts On Fi Brinolytimentioning
confidence: 86%
“…These results indicate that the anticoagulating effect of the extracts from heshiko and narezushi is closely related to the acceleration of fi brinolysis via the increase of tPA activity and the decrease of PAI-1 activity. Antihypertensive and hypocholesterolemic effects of the extracts from heshiko and narezushi were likely to be attributable waterextractive components including peptides produced during processing (26)(27)(28)(29). Therefore, the water-extractive components including peptides produced by protein hydrolysis during processing also may enhance tPA activity through the inhibition of PAI-1 activity directly or through hypotensive and hypolipidemic effects.…”
Section: The Effect Of Heshiko and Narezushi Extracts On Fi Brinolytimentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] Author already reported hypotensive and hypocholesterolemic effects as physiological functions of crude water-extractive components (extracts) from heshiko and narezushi. [18][19][20][21] Both heshiko and narezushi are Japanese traditional fermented products from salted mackerel, though there are some difference in their processing; the former is produced from salted mackerel by fermentation with rice-bran after salting raw mackerel with 20% weight of sodium chloride and the latter is done with boiled rice after salting raw mackerel with 5% weight of sodium chloride. Heshiko and narezushi commonly contain plenty of water-soluble components including peptides, and it was previously reported that the oral administration of heshiko and narezushi extracts delayed blood coagulation in rats in which the acceleration in fibrinolysis via increased tPA activity was involved.…”
Section: Introductionmentioning
confidence: 99%